The Weimar Republic, 1919-1933 - Henig, Ruth B. (Ruth Beatrice) (Lancaster pamphlets., 1998)
A study of Germany between the wars, examining the aims of the new republic, their failure, and how they led to Nazism, and eventually World War II. Henig includes an outline of the historiography and the changing attitudes to the Weimar Republic.